Reproductive biology of the Indian sandwhiting, Sillago sihama (Forsskal) - maturity stages, fecundity, spermatozoa and histology of gonads - Vinod, B. H.; Basavaraja, N. (Indian Journal of Fisheries, 2011)
An attempt was made to gather data on certain reproductive traits of the sand whiting, Sillago sihama (family: Sillaginidae). The maximum weight recorded for male and female was 77.65 and 76.9 g respectively, while the maximum length obtained was 21.70 and 21.96 cm respectively. The highest percent of gravid females was found during September-October. The gonadosomatic index (GSI) of females was marginally higher (3.84±5.8) than that of males (2.09±0.2); there was no significant difference in GSI of male and female (p>0.05), except in the months of April and July. The highest percentage of mature fish was recorded in June. The results confirm that S. sihama is a continuous breeder with two peak breeding seasons, one during May - June and the other during August - December. The absolute fecundity varied between 24,439 and 59,372 eggs/female, whereas the relative fecundity was observed to be between 4,29,953 and 8,66,968 eggs/kg body weight. The ova-diameter showed very little variation (0.32-0.46 mm) between individual females. Higher spermatozoa motility (97%) and duration (164 s) were observed in the month of July and higher level was maintained through November at 25 and 28 ppt saline water. The spermatozoa density (9.28 × 106 – 10.18 × 106 nos. ml-1) and spermatocrit (44.83 – 46.15%) were high during the same period. The results also indicate a direct relationship between the two characteristics. Histological examination of ovary of S. sihama revealed the presence of oocytes at different stages of maturity. The immature gonads showed maximum percentage of oogonia, while the mature gonad had maximum proportion of mature and vitellogenic atretic oocytes. The spent ovary showed fewer oogonia, vitellogenic atretic oocytes and corpus luteum. Histology of the testis indicated the presence of male germ cells such as spermatogonia, spermatids, spermatocytes and spermatozoa depending upon the stage of maturity, with the testis of spent fish showing the presence of more or less empty seminiferous lobules with few residual spermatozoa.